Inshore marine coastal zone migration patterns in Atlantic salmon post‐smolts emigrating from eight rivers in north‐east Scotland - Colin E. Adams; Ruaidhri Forrester; Matthew Newton; Angus J. Lothian; Hannele M. Honkanen; Davide Thambithurai; Lorna Wilkie; Melanie A. Smith; Marcus Walters; Richard Miller; Karen Muller; Brian Shaw; et al. (Journal of Fish Biology, 2026)
Atlantic salmon, Salmo salar , migrate through multiple habitat types, each having the potential to impact differently upon migration success. The inshore marine coastal zone is arguably disproportionately impacted by potential stressors on populations. We investigated the migration of Atlantic salmon post‐smolts ( n = 898) from eight rivers (populations) through the inshore marine coastal zone over a 2‐year period using acoustic telemetry. Migration success through marine inlets where fish first entered seawater, and through the wider inshore marine coastal area (the Moray Firth, north‐east Scotland) was consistently high across populations and across years (mean = 77%). There was no evidence of the high inshore marine predation rates reported elsewhere. Post‐smolts utilised well‐defined inshore marine migration pathways that were broadly consistent among populations and over time. The pace of migration through the inshore marine coastal habitat was also consistently rapid across populations and time, with the period of migration being seasonally constrained (mean across population = 36.5; range 18–45 days). Taken together with existing literature, this study suggests that the patterns of migration of Atlantic salmon post‐smolts through the inshore marine coastal zone are likely highly environment specific.

Future actions for the ocean acidification research community to support marine industries and coastal communities of Aotearoa New Zealand - Rachel Hale; Lea Muetzel; Jessica Ericson; Joanna Copedo; Vonda Cummings; Norman L. C. Ragg; Christina McGraw; Kim Currie; Kirsten Rodgers; Mary A. Sewell (New Zealand Journal of Marine and Freshwater Research, 2025)
Increasing atmospheric CO 2 emissions are altering the carbonate chemistry of seawater in a process known as ocean acidification (OA). This is a growing issue for marine industries and communities. During the 2023 New Zealand Ocean Acidification Community (NZOAC) Conference, the community undertook a horizon scanning exercise to determine potential future activities and opportunities. Conference participants were sent questions that focussed on topics of importance to the Aotearoa New Zealand and global OA community. Sixteen potential actions were identified. During the conference, participants voted for actions they perceived to be most important to give each an overall priority score. In order, the five top priority actions were to (i) re‐engage with policymakers to ensure OA is included in policies around climate change, oceans, fisheries, and education; (ii) maintain funding for current observation platforms; (iii) focus on solutions during engagement actions; (iv) obtain funding for new OA focused research; and (v) engage more with the public through community/public participatory science. We summarise the activities identified to address these actions and discuss potential ways forward for the NZOAC and wider research community to undertake the required research and provide much needed guidance to underpin OA mitigation and adaptation efforts.

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

Determinants of riverine migration success by Atlantic salmon ( Salmo salar ) smolts from rivers across the UK and Ireland - Jessica R. Rodger; Jemma Guthrie; Hannele M. Honkanen; Angus J. Lothian; Jessie Lilly; Marcus Walters; Richie Miller; Lorraine Hawkins; Al Reeve; Jamie Ribbens; Jim Henderson; Debbie Parke; et al. (Journal of Fish Biology, 2025)
There is some evidence that the river migration success of Atlantic salmon smolts, on their first migration to sea, varies both spatially and temporally. However, we have only a poor understanding of what may be driving this variation. In this study, we used acoustic telemetry to quantify the spatial and temporal variations in river migration success in Atlantic salmon smolts on their first migration to sea. In total 4120 Atlantic salmon smolts migrating through 22 rivers in Scotland, England, Ireland, and Northern Ireland over multiple years were included in the study. Individuals were defined as successful migrants if detected leaving the river to enter marine waters. The results show significant temporal (up to 4 years) and spatial (river) variations in migration success, with overall between‐river migration success varying from 3.4% to 97.0% and between years from 3.4% and 61.0%. Temporal variation in migration success was river specific, with some rivers being more temporally stable (exhibiting little variation between years) than others. Across all rivers and years, individual migration success was predicted positively by body condition and negatively by tag burden. The rate of migration success for a population (migration success standardized to a common river distance [proportion km −1 ]) was predicted by a number of environmental factors. The proportion of river catchment that comprised wetland and woodland positively predicted migration success, whereas the proportion of grassland and peatland in a catchment negatively predicted the rate of migration success. Although the mechanisms through which these effects may be operating were not directly examined in this study, we discuss some potential routes through which they may occur.

Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

Complex landscape, instream and anthropogenic environmental features drive genetic and morphological structuring amongst brown trout (Salmo trutta) populations in a dendritic river system - Jessica R. Rodger; Hannele M. Honkanen; Caroline R. Bradley; Patrick Boylan; Paulo A. Prodöhl; Colin E. Adams (Evolutionary Ecology, 2025)
Untangling the patterns and proximate drivers of intraspecific genetic and phenotypic structuring informs our understanding of the evolutionary processes shaping diversity. This study investigated morphological and genetic structuring of brown trout ( Salmo trutta L.) populations across varying spatial scales in a single, complex, dendritic river catchment and examined the potential natural and anthropogenic environmental features driving this structuring. Morphometric and hierarchical genetic structuring analyses of fish from 22 sampling sites in the River Foyle catchment, Ireland (~ 4500km 2 ) identified 19 morphologically distinct groups and 15 genetically distinct populations, separated by river distances ranging from 0.4 km to 188 km. Isolation by Distance was the main factor shaping both genetic and morphological divergence, indicating that strong philopatry is one of the major drivers of the observed population structuring in this system. However, both natural and anthropogenic environmental variables also explained pairwise genetic and morphological differences between sampling sites. Thus, the pairwise differences in the area of woodland in the upstream catchment, water phosphorus concentration, biological oxygen demand, catchment slope, urban area in upstream catchment, altitude, site specific percentage of canopy cover and dissolved oxygen concentration in the river channel were correlated with genetic divergence. The pairwise differences in the concentration of suspended solids, the extent of bankside overhang, the composition of bedrock, boulder and cobble substrates, watercourse width, catchment slope and site altitude were correlated with between-site morphological differences. We hypothesise that local differential selection pressures comprising both natural environmental variation and variation resulting from anthropogenic effects, in combination with strong philopatry and random genetic processes drive the clearly defined genetic and phenotypic patterns described here.

The effect of downstream translocation on Atlantic salmon Salmo salar smolt outmigration success - Ruaidhri Forrester; Hannele M. Honkanen; Jessie Lilly; Amy Green; Jessica R. Rodger; Brian A. Shields; Philip Ramsden; J. Peter Koene; Melanie Fletcher; Colin W. Bean; Colin E. Adams (Journal of Fish Biology, 2025)
Trap and transport, the capture and subsequent translocation of fish during the freshwater phase of their migration, is becoming more common as a management intervention. Although the technique can be successful, it is costly and can have unintended effects on the fish being transported. This study investigates whether trap and transport can be used to increase the migration success of Atlantic salmon, Salmo salar , smolts in naturally flowing rivers. Seaward‐migrating S. salar ( n = 294) from two UK rivers were tracked using acoustic telemetric techniques. Outmigration success and timing were compared between non‐transported (released at the original in‐river capture site) and transported (released ca. 23 km downstream of the capture site) individuals. Downstream translocation increased the proportion of fish that successfully migrated to marine waters, and there was no indication that transport reduced post‐release survival. The post‐release migration speed of transported fish was slower than expected but this was likely a function of their advanced migration timing rather than an inhibition of their capacity to migrate. These results suggest that trap and transport can increase the outmigration success of S. salar smolts, but the earlier river exit dates of transported fish could negatively affect their survival at sea.

Lake shape and the characteristics of migration behavior modify Atlantic salmon smolt migration success through lakes - Matthew Newton; Joseph McCallum; Hannele M. Honkanen; Alastair Stephen; Jessie M. Lilly; Danielle L. Orrell; Amy Green; Louise Chavarie; Jessica R. Rodger; Colin E. Adams (Journal of Fish Biology, 2025)
Migration is a high‐risk behavior. For the Atlantic salmon, Salmo salar , migrating from its river nursery area to marine feeding grounds, the magnitude of risk varies with habitat type. Passage through lakes, in particular, is associated with low rates of migration success. Downstream migrating salmon smolts are rheotactic when migrating in rivers, but lakes typically provide poorer directional currents for migrating salmon. In this study we tested if, in the absence of clear navigational cues in lakes, Atlantic salmon smolts switch to a random search strategy to find the outflowing river. We constructed random search simulations to test if lake basin shape has an effect on migration success. We also compared simulated migration characteristics with migrations of salmon smolts through five real lakes for which there are telemetry data for migrating salmon. Correlated random walk simulations showed that a random search strategy could be successful for all lake shapes tested but was more successful in curved (round and elliptical) than rectangular basin shapes. Rectangular basins with the migration start and stop points at the ends of the lake had a higher success than those where these points were perpendicular to the axis of the lake. In general, a random walk model predicted the migration success rate of fish tracked through real lakes. However, for two lakes the simulated migration success exceeded that of actual success, suggesting that fish passing through these lakes were not adopting a random search strategy. We speculate that this is the result of either conflicting navigational cues which inhibit smolts from finding the lake outlet or that they temporarily suspend migration (e.g., to feed). Modelling predicted that for small lakes, directional swimming in short steps (ca. 100 m) followed by turns with very low variation from the direction of travel resulted in the highest migration success. For larger lakes, longer step lengths but also with low turn variation (simulated turning angle drawn from distributions of standard deviation 2 ° and 5 ° around a mean of 0 ° ) resulted in the highest migration success. We conclude that navigation in downstream migrating salmon smolts switches from rheotaxis in rivers to a random search tactic in lakes except where residual flow cues in some lakes prevent this, at times resulting in suboptimal navigation outcomes.

Migration patterns and navigation cues of Atlantic salmon post‐smolts migrating from 12 rivers through the coastal zones around the Irish Sea - Jessie Lilly; Hannele H. Honkanen; Jessica R. Rodger; Diego del Villar; Patrick Boylan; Amy Green; Diego Pereiro; Lorna Wilkie; Richard Kennedy; Andrea Barkley; Robert Rosell; Niall Ó. Maoiléidigh; et al. (Journal of Fish Biology, 2024)
The freshwater phase of the first seaward migration of juvenile Atlantic salmon ( Salmo salar ) is relatively well understood when compared with our understanding of the marine phase of their migration. In 2021, 1008 wild and 60 ranched Atlantic salmon smolts were tagged with acoustic transmitters in 12 rivers in England, Scotland, Northern Ireland and Ireland. Large marine receiver arrays were deployed in the Irish Sea at two locations: at the transition of the Irish Sea into the North Atlantic between Ireland and Scotland, and between southern Scotland and Northern Ireland, to examine the early phase of the marine migration of Atlantic salmon smolts. After leaving their natal rivers' post‐smolt migration through the Irish Sea was rapid with minimum speeds ranging from 14.03 to 38.56 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal river, to 9.69–39.94 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal estuary. Population minimum migration success through the study area was strongly correlated with the distance of travel, populations further away from the point of entry to the open North Atlantic exhibited lower migration success. Post‐smolts from different populations experienced different water temperatures on entering the North Atlantic. This was largely driven by the timing of their migration and may have significant consequences for feeding and ultimately survivorship. The influence of water currents on post‐smolt movement was investigated using data from previously constructed numerical hydrodynamic models. Modeled water current data in the northern Irish Sea showed that post‐smolts had a strong preference for migrating when the current direction was at around 283° (west‐north‐west) but did not migrate when exposed to strong currents in other directions. This is the most favorable direction for onward passage from the Irish Sea to the continental shelf edge current, a known accumulation point for migrating post‐smolts. These results strongly indicate that post‐smolts migrating through the coastal marine environment are: (1) not simply migrating by current following (2) engage in active directional swimming (3) have an intrinsic sense of their migration direction and (4) can use cues other than water current direction to orientate during this part of their migration.

Modulating signalling lifetime to optimise a prototypical animal opsin for optogenetic applications - Jessica Rodgers; Phillip Wright; Edward R. Ballister; Rebecca B. Hughes; Riccardo Storchi; Jonathan Wynne; Franck P. Martial; Robert J. Lucas (Pflügers Archiv - European Journal of Physiology, 2023)
Animal opsins are light activated G-protein-coupled receptors, capable of optogenetic control of G-protein signalling for research or therapeutic applications. Animal opsins offer excellent photosensitivity, but their temporal resolution can be limited by long photoresponse duration when expressed outside their native cellular environment. Here, we explore methods for addressing this limitation for a prototypical animal opsin (human rod opsin) in HEK293T cells. We find that the application of the canonical rhodopsin kinase (GRK1)/visual arrestin signal termination mechanism to this problem is complicated by a generalised suppressive effect of GRK1 expression. This attenuation can be overcome using phosphorylation-independent mutants of arrestin, especially when these are tethered to the opsin protein. We further show that point mutations targeting the Schiff base stability of the opsin can also reduce signalling lifetime. Finally, we apply one such mutation (E122Q) to improve the temporal fidelity of restored visual responses following ectopic opsin expression in the inner retina of a mouse model of retinal degeneration ( rd1 ). Our results reveal that these two strategies (targeting either arrestin binding or Schiff-base hydrolysis) can produce more time-delimited opsin signalling under heterologous expression and establish the potential of this approach to improve optogenetic performance.

A repeated measures cognitive affective bias test in rats: comparison with forced swim test - Benjamin Aliphon; Twain Dai; Jessica Moretti; Marissa Penrose-Menz; Wilhelmina H. A. M. Mulders; Dominique Blache; Jennifer Rodger (Psychopharmacology, 2023)

Cancer surveillance for transgender and gender diverse patients with Lynch syndrome: a practice resource of the Collaborative Group of the Americas on Inherited Gastrointestinal Cancer - Rachel Hodan; Linda Rodgers-Fouche; Anu Chittenden; Mev Dominguez-Valentin; James Ferriss; Lauren Gima; Ole-Petter R. Hamnvik; Gregory E. Idos; Kevin Kline; Diane R. Koeller; Jessica M. Long; Danielle McKenna; et al. (Familial Cancer, 2023)

Investigating the behaviour of Atlantic salmon ( Salmo salar L.) post‐smolts during their early marine migration through the Clyde Marine Region - Jessie Lilly; Hannele M. Honkanen; David M. Bailey; Colin W. Bean; Ruaidhri Forrester; Jessica R. Rodger; Colin E. Adams (Journal of Fish Biology, 2022)
It is thought that survival during migration is particularly poor for Atlantic salmon post‐smolts immediately after entry into sea and particularly in the estuarine environment. Nonetheless, there is currently a lack of information on Atlantic salmon post‐smolt movement behaviour in estuaries in the UK. This study used acoustic tagging to estimate loss rates and compare the behaviour of Atlantic salmon post‐smolts migrating from two distinctly different rivers draining into the Clyde Estuary, the River Endrick ( n = 145) and the Gryffe ( n = 102). Contrary to most literature, post‐smolts undertook rapid migrations through the estuary, potentially decreasing their exposure to predators/anthropogenic stressors and reducing their estimated loss rates (river: 1%–3% km –1 ; estuary: 0.20%–0.60% km –1 ). The low loss rates in the estuary occurred despite post‐smolts engaging in passive reversal movements with the tide upon entering the estuary, possibly allowing them more time to adapt to the increased salinity. Atlantic salmon post‐smolts from both the rivers used similar migration pathways exiting into the coastal marine zone during ebbing tide. This study provides novel information on the timing and migratory routes of Atlantic salmon post‐smolts in the Clyde Estuary that can ultimately be used to inform management decisions on how to assess and reduce the potential impacts of current natural and anthropogenic stressors. Temporal repeatability of this study over multiple years is required to determine if there is variation in the factors driving the migratory patterns and loss rates of smolts in this system.

An opinion piece: the evolutionary and ecological consequences of changing selection pressures on marine migration in Atlantic salmon - Colin E. Adams; Louise Chavarie; Jessica R. Rodger; Hannele M. Honkanen; Davide Thambithurai; Matthew P. Newton (Journal of Fish Biology, 2022)
There are strong signals that the selection forces favouring the expression of long‐distance sea migration by Atlantic salmon ( Salmo salar ) are changing. Unlike many other behavioural traits, the costs of migration are incurred before any fitness benefits become apparent to the migrant. The expression of this behaviour has thus been shaped by selection forces over multiple generations and cannot respond to short interval (within a single generation) environmental change as many other behavioural traits can. Here we provide a framework to examine the evolutionary and ecological consequences of a sustained increase in migration cost. We argue that Atlantic salmon may have entered an evolutionary trap , where long‐distance sea migration has become maladaptive because of shifting environmental conditions. We predict that if higher migration costs (affecting survivorship and ultimately fitness) persist, then shifting selection pressures will result in continuing declines in population size. We suggest, however, that in some populations there is demonstrable capacity for evolutionary rescue responses within the species which is to be found in the variation in the expression of migration. Under a scenario of low to moderate change in the selection forces that previously promoted migration, we argue that disruptive, sex‐based selection would result in partial migration, where females retain sea migration but with anadromy loss predominantly in males. With more acute selection forces, anadromy may be strongly selected against, under these conditions both sexes may become freshwater resident. We suggest that as the migration costs appear to be higher in catchments with standing waters, then this outcome is more likely in such systems. We also speculate that as a result of the genetic structuring in this species, not all populations may have the capacity to respond adequately to change. The consequences of this for the species and its management are discussed.

Biological Sound Sources Drive Soundscape Characteristics of Two Australian Marine Parks - Jessica A. McCordic; Annamaria I. DeAngelis; Logan R. Kline; Candace McBride; Giverny G. Rodgers; Timothy J. Rowell; Jeremy Smith; Jenni A. Stanley; Allison Stokoe; Sofie M. Van Parijs (Frontiers in Marine Science, 2021)
Soundscapes represent an intrinsic aspect of a habitat which, particularly in protected areas, should be monitored and managed to mitigate human impacts. Soundscape ecology characterizes acoustic interactions within an environment, integrating biological, anthropogenic, climatological, and geological sound sources. Monitoring soundscapes in marine protected areas is particularly important due to the reliance of many marine species on sound for biological functions, including communication and reproduction. In this study we establish a baseline understanding of underwater soundscapes within two marine National Park Zones (NPZs) along the east coast of Australia: Cod Grounds Marine Park and an NPZ surrounding Pimpernel Rock within Solitary Islands Marine Park. In each of the NPZs, underwater recorders were deployed twice during the austral winter (33–35 days, 2018 and 60–69 days, 2019) and once during the austral summer (35–71 days, 2018–2019). We used the resulting acoustic recordings to determine hourly presence of anthropogenic and biological sounds between 20 Hz and 24 kHz and analyze their contributions to patterns of received sound levels. Sounds from vessels were recorded on most days throughout monitoring but were not found to influence long-term patterns of sound levels over their corresponding frequencies. Biological sources included dolphins, snapping shrimp, fish choruses, humpback whales, and dwarf minke whales. Dolphins, snapping shrimp, and fish choruses were present in all deployments. Median ambient sound levels showed a consistent diel pattern with increased levels resulting from crepuscular fish choruses combined with a higher intensity of snapping shrimp snaps during those times. Singing humpback whales strongly influenced the overall sound levels throughout the winter migration, while dwarf minke whales were consistently detected in the 2019 winter deployment but were only present in 2 h among the earlier deployments. Patterns of acoustic spectra were similar between the two NPZs, and patterns of soundscape measurements were observed to be driven by seasonal differences in biological contributions rather than anthropogenic sound sources, indicating that these NPZs are not yet heavily impacted by anthropogenic noise. These baseline measurements will prove invaluable in long-term monitoring of the biological health of NPZs.

Genomes of ubiquitous marine and hypersaline Hydrogenovibrio , Thiomicrorhabdus and Thiomicrospira spp. encode a diversity of mechanisms to sustain chemolithoautotrophy in heterogeneous environments - Kathleen M. Scott; John Williams; Cody M. B. Porter; Sydney Russel; Tara L. Harmer; John H. Paul; Kirsten M. Antonen; Megan K. Bridges; Gary J. Camper; Christie K. Campla; Leila G. Casella; Eva Chase; et al. (Environmental Microbiology, 2018)
Summary Chemolithoautotrophic bacteria from the genera Hydrogenovibrio, Thiomicrorhabdus and Thiomicrospira are common, sometimes dominant, isolates from sulfidic habitats including hydrothermal vents, soda and salt lakes and marine sediments. Their genome sequences confirm their membership in a deeply branching clade of the Gammaproteobacteria . Several adaptations to heterogeneous habitats are apparent. Their genomes include large numbers of genes for sensing and responding to their environment (EAL‐ and GGDEF‐domain proteins and methyl‐accepting chemotaxis proteins) despite their small sizes (2.1–3.1 Mbp). An array of sulfur‐oxidizing complexes are encoded, likely to facilitate these organisms' use of multiple forms of reduced sulfur as electron donors. Hydrogenase genes are present in some taxa, including group 1d and 2b hydrogenases in Hydrogenovibrio marinus and H. thermophilus MA2‐6, acquired via horizontal gene transfer. In addition to high‐affinity cbb 3 cytochrome c oxidase, some also encode cytochrome bd‐ type quinol oxidase or ba 3 ‐ type cytochrome c oxidase, which could facilitate growth under different oxygen tensions, or maintain redox balance. Carboxysome operons are present in most, with genes downstream encoding transporters from four evolutionarily distinct families, which may act with the carboxysomes to form CO 2 concentrating mechanisms. These adaptations to habitat variability likely contribute to the cosmopolitan distribution of these organisms.

Counterintuitive migration patterns by Atlantic salmon Salmo salar smolts in a large lake - Hannele M. Honkanen; Jessica R. Rodger; Alastair Stephen; Keith Adams; James Freeman; Colin E. Adams (Journal of Fish Biology, 2018)
What little is known about the seaward migration of Salmo salar smolt migration through standing waters indicates that it is both slow and results in high mortality rates, compared with riverine migration. This may be partly because smolts in lakes need to swim more actively and require more complex directional cues than they do in rivers. In this telemetry study of smolt migration through Loch Lomond, S. salar smolts made repeated movements in directions away from the outflowing river, which considerably increased migration time.

A gene-driven ENU-based approach to generating an allelic series in any gene - Mohamed Mohideen Quwailid; Alison Hugill; Neil Dear; Lucie Vizor; Sara Wells; Emma Horner; Shelly Fuller; Jessica Weedon; Hamish McMath; Paul Woodman; David Edwards; David Campbell; et al. (Mammalian Genome, 2004)